Genetic and nutrient modulation of acetyl-CoA levels in Synechocystis for n-butanol production - Anfelt, Josefine (Microb Cell Fact, 2015)
BACKGROUND: There is a strong interest in using photosynthetic cyanobacteria as production hosts for biofuels and chemicals. Recent work has shown the benefit of pathway engineering, enzyme tolerance, and co-factor usage for improving yields of fermentation products. RESULTS: An n-butanol pathway was inserted into a Synechocystis mutant deficient in polyhydroxybutyrate synthesis. We found that nitrogen starvation increased specific butanol productivity up to threefold, but cessation of cell growth limited total n-butanol titers. Metabolite profiling showed that acetyl-CoA increased twofold during nitrogen starvation. Introduction of a phosphoketolase increased acetyl-CoA levels sixfold at nitrogen replete conditions and increased butanol titers from 22 to 37 mg/L at day 8. Flux balance analysis of photoautotrophic metabolism showed that a Calvin–Benson–Bassham-Phosphoketolase pathway had higher theoretical butanol productivity than CBB-Embden–Meyerhof–Parnas and a reduced butanol ATP demand. CONCLUSION: These results demonstrate that phosphoketolase overexpression and modulation of nitrogen levels are two attractive routes toward increased production of acetyl-CoA derived products in cyanobacteria and could be implemented with complementary metabolic engineering strategies. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12934-015-0355-9) contains supplementary material, which is available to authorized users.